Comparison of ammonia emissions from animal wastes and chemical fertilizers after application in the soil - Majid Rostami; Stefano Monaco; Dario Sacco; Carlo Grignani; Elio Dinuccio (International Journal of Recycling of Organic Waste in Agriculture)
Background Application of different chemical fertilizers and manures is a major source of ammonia (NH3) emission. The rate and total amount of NH3 emission are related to different parameters such as climatic conditions, soil characteristics and kind of fertilizer. The current study has indicated the NH3 emission from bovine slurry, pig slurry and ammonium nitrate fertilizer after application on two soils. Two different methods were used to measure NH3 emissions: the method that use acid traps and the method that use photoacoustic infrared gas analyzer. Results In both soils the rate of NH3 emission was the greatest from the denser bovine slurry, declined in the pig slurry followed by the ammonium nitrate treatment and the control. The rate of soil infiltration could be the main factor that explained these differences. For all treatments the amount of total NH3 losses reduced in the more acidic soil. For all fertilizers the highest NH3 fluxes were measured in the first hours after spreading. A good agreement observed between the two methods is used for determining of NH3 emission. The use of a multi-gas monitor (MGM) is simple and accurate and produces a continuous series of NH3 concentration in time. Conclusion The rate and amount of NH3 emission was related to the kind of fertilizers and interaction of these treatments with soils. The results of current study confirmed that comparison of chemical fertilizers and slurry for NH3 emission is difficult because the reaction of these two groups of fertilizer is totally different